2013
DOI: 10.1097/igc.0b013e31828e425c
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, Practices, and Perceived Risk of Cervical Cancer Among Kenyan Women: Brief Report

Abstract: OBJECTIVES Eastern Africa has the highest incidence and mortality rates from cervical cancer worldwide. It is important to describe the differences among women and their perceived risk of cervical cancer in order to determine target groups to increase cervical cancer screening. METHOD In this cross-sectional study we surveyed women seeking reproductive health services in Kisumu, Kenya to assess their perceived risk of cervical cancer and risk factors influencing cervical cancer screening uptake. Chi-square s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
73
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 7 publications
21
73
2
3
Order By: Relevance
“…Nonetheless, our study is consistent with other studies done in Africa demonstrating low levels of knowledge regarding cervical cancer on the continent 18, 24 We found a significant relationship between risk perception and education and a positive correlation between both variables. This is not surprising, since it will be expected that more education will be associated with better knowledge about cancer and its risks.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Nonetheless, our study is consistent with other studies done in Africa demonstrating low levels of knowledge regarding cervical cancer on the continent 18, 24 We found a significant relationship between risk perception and education and a positive correlation between both variables. This is not surprising, since it will be expected that more education will be associated with better knowledge about cancer and its risks.…”
supporting
confidence: 83%
“…Perceived risk was also significantly associated with knowledge of risk factors and willingness to screen which was consistent with data in existing literature. 24 Notable among our findings was the fact that the higher a woman perceived her risk to be -even when she underestimated that risk -the higher her actual risk for cervical cancer was, based on objective factors. Perception of risk was also significantly related to willingness to be screened, which is consistent with existing data that establishes significance between perceived personal risk and the need for screening.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Programs also face shortages of equipment, trained personnel, and clinic and laboratory space, which result in delays in service provision and a general lack of screening coverage on the population level [11].…”
Section: Research Articlementioning
confidence: 99%
“…It detects pre-cancer cells in the early stages when it can be treated, and thus may reduce the number of deaths which occur due to cervical cancer. Although screening services are available in Kenya, many women do not go for screening and mortality rate due to cervical cancer is still high [13]. In one study it was reported that only 12.3% Kenyan women went for cervical cancer screening [14].…”
Section: Introductionmentioning
confidence: 99%